Pengaruh Angkatan Kerja, Upah, PDRB, dan Pendidikan terhadap Tingkat Pengangguran di Provinsi Banten Tahun 2002-2019 - Amgi Filiasari; Achma Hendra Setiawan (Diponegoro Journal of Economics, 2021)
Unemployment is a problem faced by every country. It has been recorded that from 2002 to 2019 the unemployment rate in Banten Province was always above the average national unemployment rate. This study aims to analyze the influence of the labor force, wages, Gross Regional Domestic Product (GRDP), and education on the unemployment rate in Banten Province in 2002-2019. This study uses secondary data in the form of time series data from 2002 to 2019 obtained from BPS and BPS Banten Province. The method of analysis in this study is multiple linear regression analysis with the Ordinary Least Square (OLS) regression method. The analysis tool used is E-views 9. The results of this study indicate that the variables of labor force, wages, and Gross Regional Domestic Product (GRDP) have a negative and significant effect on the unemployment rate in Banten Province while the education variable has a positive and significant effect on the unemployment rate in Banten Province. The dominant variable affecting on the unemployement rate in Banten Province in 2002-2019 is education.